Perlindungan Hukum Kreditur Terhadap Meninggalnya Debitur Sebelum Pendaftaran Hak Tanggungan Elektronik - Wihandriati, Wihandriati (JUSTISI, 2023)
The electronic mortgage system is expected to provide convenience for users of the system, but in its implementation it has not run optimally. One of the problems that arise is when the debtor dies after making the APHT and SKMHT which is then followed by the registration of mortgage rights. This study aims to find out how legal protection can be given to creditors against the death of the debtor before the electronic mortgage registration process is carried out. This research is a normative legal research. The data used in this study is secondary data. The collected data is then analyzed descriptively qualitatively by using a conceptual approach or concept approach. The results of this study indicate that there are two forms of legal protection for creditors against the death of the debtor prior to electronic registration of mortgage rights, namely preventive legal protection and repressive legal protection. The application of preventive legal protection is intended to prevent problems from arising in the future, while repressive legal protection is carried out with the aim of resolving disputes that arise between the parties.